144k views
3 votes
Please help with this, thankyouu

Please help with this, thankyouu-example-1
User Gfrobenius
by
4.9k points

2 Answers

3 votes

Answer:

c = 3 and n = - 7

Explanation:

Expand the left side and compare the coefficients of like terms on both sides.

(5x + 4)(2x - c) ← expand using FOIL

= 10x² - 5cx + 8x - 4c ← factor out x from each of the terms in x

= 10x² + x( - 5c + 8) - 4c

Given this is equal to 10x² + nx - 12, then

Comparing the constant terms

- 4c = - 12 ( divide both sides by - 4 )

c = 3

Comparing the coefficients of the x- terms

n = - 5c + 8 = - 5(3) + 8 = - 15 + 8 = - 7

Thus

c = 3 and n = - 7

User Dsh
by
4.7k points
4 votes

☽------------❀-------------☾

Hi there!

~

Let's solve for c.


\left(5x\ +\ 4\right)\left(2x\ +\ c\right)\ =\ 10x^(2\ )+\ nx\ -\ 12

Step 1: Add
-10x^2 to both sides.


5cx + 10x^2 + 4c + 8x + -10x^2 = nx + 10^2 - 12 + -10x^2


5cx + 4c + 8x = nx - 12

Step 2: Add
-8x to both sides.


5cx + 4c + 8x + -8x = nx - 12 + -8x


5cx + 4c = nx - 8x - 12

Step 3: Factor out variable c.


c(5x + 4) = nx - 8x - 12

Step 4: Divide both sides by
5x+4.


(c(5x +4))/(5x + 4) = (nx-8x-12)/(5x + 4)

Answer :
\boxed{(nx-8x-12)/(5x + 4) }

❀Hope this helped you!❀

☽------------❀-------------☾

User Bladimir
by
4.6k points